Atomic Force Microscopy as a Tool to Assess the Specificity of Targeted Nanoparticles in Biological Models of High Complexity. Issue 21 (28th July 2017) - Gomes, Carla P.; Lopes, Cátia D. F.; Leitner, Michael; Ebner, Andreas; Hinterdorfer, Peter; Pêgo, Ana P.
Abstract: The ability to design nanoparticle delivery systems capable of selectively target their payloads to specific cell populations is still a major caveat in nanomedicine. One of the main hurdles is the fact that each nanoparticle formulation needs to be precisely tuned to match the specificities of the target cell and route of administration. In this work, molecular recognition force spectroscopy (MRFS) is presented as a tool to evaluate the specificity of neuron‐targeted trimethyl chitosan nanoparticles to neuronal cell populations in biological samples of different complexity. The use of atomic force microscopy tips functionalized with targeted or non‐targeted nanoparticles made it possible to assess the specific interaction of each formulation with determined cell surface receptors in a precise fashion. More importantly, the combination of MRFS with fluorescent microscopy allowed to probe the nanoparticles vectoring capacity in models of high complexity, such as primary mixed cultures, as well as specific subcellular regions in histological tissues. Overall, this work contributes for the establishment of MRFS as a powerful alternative technique to animal testing in vector design and opens new avenues for the development of advanced targeted nanomedicines. Abstract : Evaluation of neuron‐targeted trimethyl‐chitosan nanoparticles specificity toward neuronal cell populations in samples of different complexity and biological relevance by molecular recognition force spectroscopy (MRFS). This work puts forward MRFS as a valuable tool for the design and characterization of new targeted formulations that will lead to the development of more robust and advanced nanomedicines.